The InBIO Barcoding Initiative Database: contribution to the knowledge of DNA barcodes of the vascular plants of north-eastern Portugal - João Queirós; Rodrigo Silva; Catarina J. Pinho; Hélia Vale-Gonçalves; Ricardo Pita; Paulo Alves; Pedro Beja; Joana Paupério; Miguel Porto (Biodiversity Data Journal, 2025)
Metabarcoding is invaluable for understanding trophic interactions, enabling high-resolution and rapid dietary assessments. However, it requires a robust DNA barcode reference library for accurate taxa identification. This dataset has been generated in the framework of the InBIO Barcoding Initiative (IBI) and Agrivole project. The integration of these two projects was crucial, as Agrivole aimed to investigate the trophic niche of small mammals in Trás-os-Montes Region through DNA metabarcoding, which required a reliable plant DNA barcode library for this same region. Given the large number of species not yet represented in international databases, a survey of local plants was essential to fill this gap. Thus, this study created an accurate DNA reference database for the plants of the Trás-os-Montes Region of Portugal.The current DNA reference database contains 632 vascular plant samples, all morphologically identified and belonging to 435 species. This represents 14% and 38.7% of the total known plant species for Portugal and the study area, respectively.Of the 1781 barcode sequences provided in this dataset, 1099 contain new information (61.7%) at different levels: 254 (13.6%, ITS2: 41, trnL-ef: 126, trnL-gh: 87) are completely new to GenBank and/or BOLD databases at the time of publication, 438 (24.6%, ITS2: 59, trnL-ef: 173, trnL-gh: 206) are new records for a given species and 407 (22.9%, ITS2: 187, trnL-ef: 206, trnL-gh: 14) provide additional information (e.g. different bp length, intraspecific genetic variability); the remaining 682 sequences (38.3%) are equal (100% identity) to sequences already publicly available for the identified species. Overall, this dataset represents a significant contribution to the genetic knowledge of vascular plants represented in public libraries. This is one of the public releases of the IBI database, which provides genetic and distributional data for several taxa.All vouchers are deposited in the Herbarium of the Museum of Natural History and Science of the University of Porto (MHNC-UP) and their DNA barcodes are publicly available in the Barcode of Life Data System (BOLD), NCBI GenBank online databases and International Nucleotide Sequence Database Collaboration (INSDC).